2021
DOI: 10.3390/ijms22168622
|View full text |Cite
|
Sign up to set email alerts
|

Uteroplacental Circulation in Normal Pregnancy and Preeclampsia: Functional Adaptation and Maladaptation

Abstract: Uteroplacental blood flow increases as pregnancy advances. Adequate supply of nutrients and oxygen carried by uteroplacental blood flow is essential for the well-being of the mother and growth/development of the fetus. The uteroplacental hemodynamic change is accomplished primarily through uterine vascular adaptation, involving hormonal regulation of myogenic tone, vasoreactivity, release of vasoactive factors and others, in addition to the remodeling of spiral arteries. In preeclampsia, hormonal and angiogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 318 publications
(400 reference statements)
0
16
0
5
Order By: Relevance
“…PE has a great impact on growth and development of the fetus, impairs the structure and function of fetal cardiovascular system or kidney, and causes hypertension. 15 Current studies suggest that the pathogenesis of PE may be related to decidual macrophage dysfunction, 16 placental angiogenesis disorder, 17 placental aging, 18 , 19 protein aggregation, and defective placental aggregation phagocytosis. 20 At the molecular level, the microRNA spectrum of blood exosomes has been used to evaluate the pathophysiology of preeclampsia and predict the disease, 21 and there are more and more studies at gene level.…”
Section: Discussionmentioning
confidence: 99%
“…PE has a great impact on growth and development of the fetus, impairs the structure and function of fetal cardiovascular system or kidney, and causes hypertension. 15 Current studies suggest that the pathogenesis of PE may be related to decidual macrophage dysfunction, 16 placental angiogenesis disorder, 17 placental aging, 18 , 19 protein aggregation, and defective placental aggregation phagocytosis. 20 At the molecular level, the microRNA spectrum of blood exosomes has been used to evaluate the pathophysiology of preeclampsia and predict the disease, 21 and there are more and more studies at gene level.…”
Section: Discussionmentioning
confidence: 99%
“…It is well‐known that E2 and T are associated with vascular remodeling. 40 , 41 Accordingly, abnormal E2 or T may affect the placental function and lead to PE in the early stage of placental development, but the mechanism remains to be further studied. Our study revealed that sPE may be related to the concentration of T and E2, but especially the balance of E2/T.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that 80% to 90% of total uteroplacental blood flow perfuses the placenta at term and the remaining supplies the myometrium [ 175 , 188 , 189 ], providing sufficient nutrient and oxygen supply for the growth of the placenta and fetus. The hemodynamic changes in the uteroplacental circulation during pregnancy are primarily achieved by uterine vascular remodeling, reduced uteroplacental vascular resistance, and the formation of the placenta [ 8 , 9 , 190 , 191 , 192 ]. Notably, a variety of functional changes contribute to the adaptation.…”
Section: Adaptation/maladaptation Of the Uteroplacental Circulation I...mentioning
confidence: 99%
“…Uteroplacental blood flow is inversely proportional to uteroplacental vascular resistance. Increased uteroplacental blood flow in pregnancy is primarily achieved by lowering uteroplacental vascular resistance owing to the structural remodeling of spiral arteries, establishment of the placenta, and vasodilation [ 8 , 9 ]. Adaptive changes in the uteroplacental circulation are impaired in pregnancy complications such as preeclampsia, fetal growth restriction (FGR, also known as intrauterine growth restriction), and gestational diabetes, leading to insufficient perfusion of the placenta [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%